Examining the Role of Makindye-Based Radio Stations in Creating Awareness on Sanitation Practices in Kampala Uganda - Maidunoma, Zannah; Gaji, Zannah Baba; Falmatami, Kyari Sheriff (NIU Journal of Humanities; Vol 2 No 2 (A) (2017): KIU Journal of Humanities, Vol. 2 No. 2 (A), December 2017, 2018)
The study was conducted between the months of June-August, 2017 to examine the role of Makinde-based Radio stations in creating awareness on sanitation practices in Kampala, Uganda. The study was conducted in five settlements randomly selected within the Makindye Division including Kansanga, Bukasa, Ggaba, Kabalaga-Kataba and Nsambiya-Gogonya. Agenda setting theory was used to underpin this study. Radio campaigns are strong instrument in raising public awareness on environmental related issues however, the role played by most of the Makinde-based Radio stations seem to be very low. Hence, this study was aimed to assess the roles of these Radio stations. A total of 400 respondents comprising of 395 local community people and 5 officials each from 5 different Makinde-based Radio stations selected using Purposive sampling technique. Descriptive Survey design was used. Data collection instruments used were Questionnaires and structured Interview Guide. All quantitative data collected was analyzed in SPSS using descriptive statistics. Some of the findings revealed that Radio programmes enhanced people’s awareness on sanitation practices (mean value 2.614. std. 1.26), enabled people to understand how to best relate to the environment (mean value 3.76, std..952). Based on these findings and others not mentioned here, it is highly recommended that, since positive attitude toward sanitation practices depended on regular radio enlightenment campaigns, frequent campaigns by the media were highly recommended.